Worldwide destinations : the geography of travel and tourism - Boniface, Brian G., ....-; Cooper, Christopher Paul, 1952-; Cooper, Robyn, ....- (Milton Park, Abingdon, Oxon ; New York : Routledge, 2021)
Worldwide Destinations: The Geography of Travel and Tourism is a unique text that explores tourism demand, supply, organisation and resources for a comprehensive range of destinations worldwide. The eighth edition is brought up to date with features such as: An exploration of current issues such as climate change, overtourism, expedition cruises, film tourism, economic and cultural impacts of tourism. New and updated case studies throughout. More emphasis on South-east Asia, Africa and the Middle East. Online resources for lecturers and students including PPTs, web links, video links and meditations on the evolving implications of COVID-19 for tourism. The first part of the book comprises thematic chapters which detail the geographic knowledge and principles required to analyse the tourism appeal of destinations. The subsequent division of the book into regional chapters enables the student to carry out a systematic analysis of a particular destination, by providing insights on cultural characteristics as well as information on specific places. Worldwide Destinations: The Geography of Travel and Tourism is an invaluable resource for studying every destination in the world, by explaining tourism demand, evaluating the many types of tourist attractions and examining the trends that may shape the future geography of tourism. This thorough guide is a must-have for any student undertaking a course in travel and tourism.
First published as the Worldwide destinations casebook. 2005.
Includes bibliographical references and index.
Keywords: Reisbestemmingen; Tourism; Travel